Convergence of Corporate Social Responsibility and Corporate Governance in Weak Economies: The case of Bangladesh - Rahim, Mia Mahmudur (Journal of business ethics, 2014)
The convergence of corporate social responsibility (CSR) and corporate governance (CG) has changed the corporate accountability mechanism. This has developed a socially responsible ‘corporate self-regulation’, a synthesis of governance and responsibility in the companies of strong economies. However, unlike in the strong economies, this convergence has not been visible in the companies of weak economies, where the civil society groups are unorganised, regulatory agencies are either ineffective or corrupt and the media and non-governmental organisations do not mirror the corporate conscience. Using the case of Bangladesh, this article investigates the convergence between CSR and CG in the self-regulation of companies in a less vigilant environment.